The standards-based integrated library a collaborative approach for aligning the library program with the classroom curriculum - Miller, Donna P. 1948- (Gale virtual reference library, 2004)
A handbook that describes a specific collaborative process for library media specialist and classroom teacher to use in planning teaching units. Written for K-12 educators. Also provides suggested book lists, web sites, and professional resources.